2018
DOI: 10.1177/0956462418767188
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection, high-risk behaviors and substance use in homeless men sheltered in therapeutic communities in Central Brazil

Abstract: Homeless men present high vulnerability to HIV infection, mainly due to sexual risk behaviors and substance use. The objective was to estimate the prevalence of HIV infection, risk behaviors and substance use in homeless men. A cross-sectional study was conducted in 481 homeless men recruited in four therapeutic communities in the Goiás State, Central Brazil. All were interviewed about sociodemographic characteristics, substance use, and risk behaviors. Furthermore, all were tested for HIV. Poisson regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
0
10
2
4
Order By: Relevance
“…Despite frequent alcohol and drug use of homeless persons have been already observed in Brazil and worldwide [20,26,82,83] and with higher infection risk to HIV and T. gondii in general population studies [41,84,85], there was no statistical association observed in the present study. Although one HIV-positive homeless person herein with multiple infections also declared himself as alcohol, marijuana, and skunk cannabis user, the other HIV-positive homeless persons denied alcohol and drug use.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Despite frequent alcohol and drug use of homeless persons have been already observed in Brazil and worldwide [20,26,82,83] and with higher infection risk to HIV and T. gondii in general population studies [41,84,85], there was no statistical association observed in the present study. Although one HIV-positive homeless person herein with multiple infections also declared himself as alcohol, marijuana, and skunk cannabis user, the other HIV-positive homeless persons denied alcohol and drug use.…”
Section: Discussioncontrasting
confidence: 71%
“…In Brazil, out of 247,795 reported HIV cases between 2007 and 2018, 117,415 (47.4%) persons were from the southeastern region, where Sao Paulo is located [24]. Studies in Brazilian general homeless population have shown HIV positivity in 6/330 (1.8%) and 69/1,405 (4.9%) individuals of Sao Paulo city, and 6/481 (1.2%) in another city of central-western Brazil [20,25,26]. In two studies of homeless populations co-infected with HIV and tuberculosis, prevalence varied from 4.4% in Minas Gerais to 17.3% in São Paulo, both southeastern Brazilian states [20,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Still, Brazilian regions in 2018, presented variable rates of HIV infection with 5,084 (11.6%) in the North region, 10,808 (24.6%) cases in the Northeast region, 16,586 (37.7%) in the region Southeast, 7,838 (17.8%) in the South and 3,625 (8.2%) in the Midwest 7 . In the central-western region of Brazil, an HIV prevalence of 1.24% was detected, with a signi cant association in relation to previous HIV tests and years of schooling 3 . In the southeastern region, in a similar population, the prevalence was 4.9%, with the majority being male (85.6%), non-white (71.5%), with a mean age of 40.9 years and low education (72.0%) 8 .…”
Section: Introductionmentioning
confidence: 95%
“…Given the magnitude of the problem, homeless people are more vulnerable to HIV infection, considering sexual risk behaviors and substance use 3 . Worldwide, the prevalence of HIV is different in relation to the population and risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As human immunodeficiency virus (HIV) disproportionately impacts populations that suffer from health disparities, these marginalized people often face an increased risk of HIV infection compared to that of the general population. Findings [611] suggest that the overall prevalence rates of HIV infection among homeless people (1.24 to 1.7%), sex workers (8 to 17.3%) and drug users (17.7 to 34%) are relatively high. The estimated HIV prevalence in adults aged 15–49 years worldwide at the end of 2017 was 0.8% [12].…”
Section: Introductionmentioning
confidence: 99%